Author Response: One-Stage, Limited-Resection Epilepsy Surgery for Bottom-of-Sulcus Dysplasia. (13th December 2022) - Harvey, A. Simon; Macdonald-Laurs, Emma
Abstract : We thank Dr. Hu and colleagues for their encouraging comments on our article. 1 Both of our groups advocate minimal, targeted resections of bottom-of-sulcus dysplasia (BOSD), 1, 2 and we further promote omitting intracranial EEG monitoring in MRI-positive cases. As noted in references 41–45 in our article, laser interstitial thermal therapy (LITT) and stereotactic thermocoagulation (STC) are reported in BOSD to further minimize surgical intervention and are appropriate for medial, basal frontal, and parietal BOSDs—occurrences which are not as easily accessed with small craniotomy as BOSD on the cerebral convexity. STC is typically undertaken in patients who undergo prior stereo-EEG with an electrode directly sited in an MRI-positive BOSD. The potential disadvantages of LITT and STC are the lack of confirmation of epileptogenicity with electrocorticography, a pathologic diagnosis from histopathology, and identification of genetic variants from deep sequencing of tissue.